2019
DOI: 10.1183/23120541.00112-2019
|View full text |Cite
|
Sign up to set email alerts
|

Home-based tuberculosis contact investigation in Uganda: a household randomised trial

Abstract: IntroductionThe World Health Organization (WHO) recommends household tuberculosis (TB) contact investigation in low-income countries, but most contacts do not complete a full clinical and laboratory evaluation.MethodsWe performed a randomised trial of home-based, SMS-facilitated, household TB contact investigation in Kampala, Uganda. Community health workers (CHWs) visited homes of index patients with pulmonary TB to screen household contacts for TB. Entire households were randomly allocated to clinic (standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
2
39
0
1
Order By: Relevance
“…As previously reported [ 30 ], the mHealth trial showed no improvement in the primary outcome of completing TB evaluation. Although household contacts and health workers spoke positively about the mobile app and text messaging, low rates of delivery and uptake of text-messaged instructions were observed [ 26 , 31 ].…”
Section: Methodssupporting
confidence: 60%
“…As previously reported [ 30 ], the mHealth trial showed no improvement in the primary outcome of completing TB evaluation. Although household contacts and health workers spoke positively about the mobile app and text messaging, low rates of delivery and uptake of text-messaged instructions were observed [ 26 , 31 ].…”
Section: Methodssupporting
confidence: 60%
“…Where these costs are large and must be incurred before scale-up is certain, they may represent a majority of the total cost of the intervention. For example, in a trial of mobile Health-facilitated home-based contact investigation for TB in Uganda, a software package was required to generate short messaging service (SMS) reminders to facilitate home-based screening, incurring large up-front costs for an initial service contract and adaptation to the Ugandan telecommunications infrastructure [ 15 ]. While this intervention was only delivered to 372 households (919 contacts screened), the cost of designing and developing the intervention ($137 per contact screened, of which $90 was for software development) overshadowed the cost of intervention delivery ($54 per contact screened) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cluster RCT in Kenya demonstrated that correct artemether-lumefantrine (AL) management improved by 23.7% (95% confidence interval (CI) = 9.0-33.7, P = 0.0007) immediately after the intervention and by 24.5% (95% CI = 11.6-35.7, P = 0.0001) six months after the intervention when text message reminders were sent to the CHWs on following national malaria management guidelines [ 53 ]. Authors of the same study also determined the cost-effectiveness of the use of these text message reminders on adherence to national malarial treatment guidelines and demonstrated the cost per additional child correctly managed was US$0.50 under study conditions, US$0.36 if implemented by the ministry of health in the same study locations under routine, and USD 0.03 if implemented nationally after being scaled-up [ 37 ].…”
Section: Resultsmentioning
confidence: 99%